Co-Fe dual-atom isolated in N-doped graphydine as an efficient sulfur conversion catalyst in Li-S batteries - Parsaee, Faeze; Fayzullaev, Normurot; Nassar, Maadh Fawzi; Alreda, Baraa Abd; Mahmoud, HassabAlla M.A.; Taki, Anmar Ghanim; Faraji, Monireh (Elsevier, 2024)
Lithium-sulfur (Li-S) batteries have garnered considerable attention as a prospective energy storage device for the future due to their exceptionally high theoretical energy density. Unfortunately, sluggish sulfur reactions create a bottleneck in Li–S batteries, hindering their ability to deliver all their promised energy. In this work, we reported the N-doped graphydine as a sulfur host in a Li-S battery cathode. The graphydine host is decorated with isolated cobalt/iron dual-atom catalyst. Co/Fe sites in Li–S batteries play a double role as an electrocatalyst, speeding up the two-way conversion between sulfur and lithium sulfide during the battery's cycle. These composite electrocatalysts, built with a remarkable 70 wt% sulfur content, achieve a high specific capacity of 1520 mA h g⁻¹ at a low charging current density (0.1 C). At a low current density of 0.1 C, they present remarkable cycling consistency, losing only 0.07% of capacity for each cycle for 1000 cycles.